Resistance of Some Rice Varieties (Oryzae sativa Linnaeus) to the Brown Planthopper (Nilaparvata lugens Stal) using the Honey Dew Test: Uji Ketahanan Beberapa Varietas Padi terhadap Wereng Batang Coklat (Nilaparvata lugens Stal) Populasi Karawang Menggunakan Metode Embun Madu - Sari, Widya Puspita; Rinaldi, James; Darmadi, Dedi; Arneti, Arneti (Jurnal Proteksi Tanaman (Journal of Plant Protection), 2022)
One of the control techniques for the brown planthopper or BPH (Nilaparvata lugens Stal) is resistant varieties. This study aimed to determine the resistance level of several rice varieties (Oryza sativa Linnaeus) to the BPH of the Karawang Population. The study was located at the Entomology Laboratory, Center for Predicting Plant Pest Organisms (BBPOPT) Jatisari, Directorate General of Food Crops, Ministry of Agriculture, Indonesia, from July to August 2022. The study was conducted in a Completely Randomized Design (CRD) with ten treatments and five replications. The treatment was in the form of different rice varieties (Pelita, Inpari-33, Inpari-47, Inpari-48, Ciherang, Cilamaya Muncul, Mapan, Situ Bagendit, M-400, IR-64). Parameters observed were spot area, spot area conversion, and determination of resistance. The results showed that the resistance of some of the tested rice varieties to BPH of the Karawang population was classified as moderate to moderately resistant. Inpari-47, Inpari-48, IR-64, M-400, Inpari-33, Cilamaya Muncul, and Situ Bagendit are moderately resistant, while Mapan, Ciherang, and Pelita have moderate resistance. The results of the honeydew test can be compared with other resistance test methods.